The Correlation Between Risk Perception, Outcome Expectancies, Task Self-Efficacy, And Intention With Dietary Compliance In Type 2 DM Patients - Tajaruddin, Muhammad; Solehin, Muhammad Mukhlis; Aufa, Naimatul; Negara, Candra Kusuma (Sean Institute, 2024)
Compliance of DM patients in Indonesia to diet is still relatively low. Dietary non-compliance can worsen the patient's condition, cause complications and reduce quality of life. Factors that influence dietary compliance are motivation, self-efficacy, knowledge, intention, and family support. This study aims to analyze the correlation between risk perception, outcome expectancies, task self-efficacy, and intention with dietary compliance in patients with type 2 Diabetes mellitus. The study used a cross-sectional approach. The research sample was collected using the cluster sampling method and obtained 150 respondents. Data were analyzed using spearman rho statistical analysis (α≤0.05) there was a significant correlation between risk perception (p=0.000), outcome expectancies (p=0.000), task self-efficacy (p=0.000), and intention (p=0.000) with dietary compliance in patients with type 2 DM. Risk perception, outcome expectancies, task self-efficacy, and intention were significantly related to DM diet compliance. Therefore, it is necessary to improve the risk perception, outcome expectancies, task self-efficacy, and intention factors, through counseling activities that focus on the four factors above, so that glycemic control behavior with a DM diet can improve for the better.